SYSTEMATIC LITERATURE REVIEW ON QR CODE IMPLEMENTATION FOR GOVERNMENT INVENTORY MANAGEMENT SYSTEMS - Geraldo Nathaniel; Gunawan Ari Nursanto; Okky Pratama Martadireja (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to systematically review various literature related to the design and development of a web-based office stationery (ATK) management application utilizing QR-Code technology. The research focuses on the implementation of this system at the Class I Non-TPI Immigration Office in Bekasi as an effort to support the efficiency of APBN (State Budget) utilization. This study collects, filters, and analyzes articles, journals, and other academic sources relevant to the topic to provide a comprehensive overview of the benefits, challenges, and methodologies for designing digital systems in government environments. The review results indicate that a QR-Code-based system can reduce recording errors, accelerate administrative processes, and enhance transparency in budget usage. Additionally, the implementation of this technology supports the digital transformation of bureaucracy, aligning with the government's budget efficiency policies. The findings from the reviewed literature provide a theoretical foundation for the proposed system's development and highlight the importance of integrating information technology into ATK inventory management to optimize operational efficiency and budget utilization.